Ambiguous Entanglements: Infrastructure, Memory and Identity in Indigenous Evenki Communities along the Baikal-Amur Mainline - Povoroznyuk, Olga (Social Anthropology, 2023)
The Baikal– Amur Mainline (BAM) project has been the embodiment of (post‐ )Soviet modernisation with its promises of economic prosperity, mobility and connectivity. It boosted regional development and intro-duced new forms of mobility, but also accelerated sedentarisation, assimilation and social polarisation among Evenki, an indigenous people who had been living in the region long before the arrival of the megaproject. Complex and often ambiguous entanglements of Evenki with the BAM infrastructure – from participation in construction to the exchange of goods to loss of reindeer and land, shaped indigenous ways of life, memories and identities. The master‐ narrative of the BAM seems to have been internalised by many Evenki and to have drowned out critical voices and indigenous identities. In this article, I direct attention to ‘hidden transcripts’, thereby giving voice to underrepresented memories and perspectives on the BAM within Evenki communi-ties. Drawing on ethnographic materials and interviews with indigenous leaders, reindeer herders and village residents, who experienced the arrival of the BAM and have been entangled with the railroad in various ways, I seek to contribute to a critical and comprehensive history of the BAM and to explore the construction and articulation of indigenous identities vis‐ à‐ vis large‐ scale infrastructure and development projects.